Livelihood diversification among women farmers in Nigeria’s flood-resilient drylands - Ummi Khalthum Mohammed; Nicola Favretto (Climate Risk Management)
Jigawa State, Nigeria, faces increasing vulnerability to recurrent floods, highlighting the need for alternative socio-economic strategies to enhance livelihood diversification and strengthen the resilience of the most vulnerable groups, particularly women farmers. This study explores the role of livelihood diversification in flood resilience through three key questions: (1) How frequent are floods in northern Nigeria, and what are their perceived impacts? (2) What livelihood diversification strategies do women farmers employ? and (3) What factors enable or hinder the adoption of diversified livelihoods? Data was collected via focus group discussions with women farmers from three communities, supplemented by semi-structured interviews with community leaders and institutional stakeholders, and analysed using coding and content analysis. Results on reported perceptions show that from 2013 to 2023 communities experienced an average of seven flood events, causing significant damage to homes and farmland. Women farmers diversify livelihoods by rotating fast-growing crops (e.g., beans, tomatoes, cassava), planting economic trees, raising livestock, and engaging in off-farm activities like petty trading. Enabling factors include building farmer and institutional stakeholders’ capacity, improving climate data access, supporting alternative income activities, strengthening agricultural extension, and providing infrastructural and financial support. However, barriers such as limited access to capital, agricultural insurance, and inequalities in resource distribution among women, along with cultural dynamics and conflicts, hinder progress. Awareness-raising and capacity-building are essential to overcoming these challenges and addressing social barriers. Additionally, limited institutional coordination and inadequate budgetary allocations exacerbate difficulties in achieving effective livelihood diversification for flood resilience. By revealing the factors influencing the resilience and vulnerability of rural women amid recurring floods in dryland Africa, the lessons learned help bridge key knowledge gaps and highlight essential enablers for strengthening adaptive capacities in flood-prone areas.